Sitosterolemia in pregnancy: A rare lipid disorder and its obstetric management - Kanagavarshani Murali; Sai Vidya Muthineni; Sasirekha Rengaraj; Veena Pampapati; Sanjay Sriram (Obstetric Medicine, 2026)
Sitosterolemia is an autosomal recessive condition leading to increased absorption of plant sterols from the intestine. A woman in her first pregnancy presented with thrombocytopenia and a family history of sitosterolaemia. Genetic analysis confirmed an ABCG8 (G-ATP binding cassette transporters) mutation. She was started on ezetimibe and had no complications other than thrombocytopenia. She underwent an emergency cesarean delivery at 37 weeks of gestation. Post-operatively both the mother and the baby did well. While sitosterolaemia is not directly linked to pregnancy complications such as diabetes and pre-eclampsia, its impact on lipid metabolism can indirectly increase the risk. It is important to distinguish it from familial hypercholesterolemia as sitosterolemia responds better to ezetimibe and is relatively non-responsive to statins. This case report shows that sitosterolemia, though an uncommon diagnosis, can manifest in many ways, in this case being thrombocytopenia. With dietary modifications and appropriate therapy, these patients can have a normal pregnancy.